An Episode of Acute Mortality in Laboratory Zebrafish- A Case Report (Journal of Laboratory Animal Science, 2022)
In the recent years, zebrafish (Danio rerio) species has been popularized as an animal model of human biology in  understanding the genetic mechanism of vertebrate development and disease. Aquarium water is an immediate surrounding  medium for the fish species in laboratory setup that determine their survival and normal physiological activities. Raising  healthy zebrafish in the laboratory environment is prerequisite to ensure disease free stock for better research outcome.  Important water parameters such as temperature, pH, electric conductivity, salinity, dissolved oxygen and CO2 are required  to be monitored regularly as a part of quality control. An episode of acute mortality was witnessed in several lines of  laboratory zebrafish maintained at the facility of TIFR, Mumbai. The clinical symptoms include lethargy, swimming  inability, settling down at the bottom and acute death. The acute mortality was evidenced irrespective of age, sex and  strains of the zebrafish. The investigation was carried out to find the etiological agents implicated in the acute mortality.  After ruling out various causative agents associated with the mortality, an investigation was zeroed on the pH of the fish  aquarium water, the culprit for the acute death episode. The highly acidic pH (3.5 to 4.0) of the fish aquarium water was  brought to normal level by adding buffer solution to avoid further mortality. Present paper describes an episode of acute  death, timely diagnosis and successful measures taken to rescue the Danio rerio loss due to highly acidic aquarium water.
Keywords: Danio rerio; Aquaria; CWRS; water quality